1984
DOI: 10.1063/1.95028
|View full text |Cite
|
Sign up to set email alerts
|

A 14% efficient nonaqueous semiconductor/liquid junction solar cell

Abstract: We describe the most efficient semiconductor/liquid junction solar cell reported to date. Under W-halogen (ELH) illumination, the device is a 14% efficient two-electrode solar cell fabricated from ann-type silicon photoanode in contact with a nonaqueous electrolyte solution. The cell's central feature is an ultrathin electrolyte layer which simultaneously reduces losses which result from electrode polarization, electrolyte light absorption, and electrolyte resistance. The thin electrolyte layer also eliminates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
79
0

Year Published

1987
1987
2017
2017

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 92 publications
(82 citation statements)
references
References 16 publications
3
79
0
Order By: Relevance
“…52,18 The unique reactivity of HSi(111) surfaces with alcohols, including CH 3 OH, has been exploited as a versatile method to impart a desired functionality to the surface via the robust Si-O bond, without formation of a thick insulating silicon oxide layer on the surface. For example, n-Si/CH 3 OH junctions have yielded high open-circuit voltages (632-640 mV) and high device efficiencies (12-14%) [53][54] in regenerative photoelectrochemical cells, with the device performance correlated with low surface recombination velocities [55][56][57] as well as the favorable band-edge positions 58 of the methoxylated Si surface. The methoxy termination can moreover be converted to F-termination or OHtermination,5 double-side polished, 300 ± 25 µm thick, oriented within 0.5° of the (111) crystal plane, and had a resistivity of 0.40 Ω cm.…”
Section: -49mentioning
confidence: 99%
“…52,18 The unique reactivity of HSi(111) surfaces with alcohols, including CH 3 OH, has been exploited as a versatile method to impart a desired functionality to the surface via the robust Si-O bond, without formation of a thick insulating silicon oxide layer on the surface. For example, n-Si/CH 3 OH junctions have yielded high open-circuit voltages (632-640 mV) and high device efficiencies (12-14%) [53][54] in regenerative photoelectrochemical cells, with the device performance correlated with low surface recombination velocities [55][56][57] as well as the favorable band-edge positions 58 of the methoxylated Si surface. The methoxy termination can moreover be converted to F-termination or OHtermination,5 double-side polished, 300 ± 25 µm thick, oriented within 0.5° of the (111) crystal plane, and had a resistivity of 0.40 Ω cm.…”
Section: -49mentioning
confidence: 99%
“…For many types of photoelectrodes, forced convection produced by rapid stirring in a three-electrode configuration (20), or effective diffusive transport produced by use of a well-designed two-electrode thin-layer cell configuration (10,(21)(22)(23), have been utilized to minimize mass transport losses between the photoelectrode and the counter electrode (Scheme 1 A and B). However, these approaches do not effectively minimize losses due to restricted mass transport in the internal volume of microstructured photoelectrodes, such as Si wire arrays.…”
mentioning
confidence: 99%
“…In contrast to the case of acetonitrile and other non-aqueous solvents, nSi/electrolyte junctions prepared in methanol lead to stable junctions. The Schottkybarrier height and the photopotential depend on the potential of the redox system as expected for an ideal semiconductor/electrolyte junction (142), allowing for the elaboration of stable and efficient n-Si/redox system photoelectrochemical cells (143). It has been shown that this good result is actually due to a chemical modification of the silicon surface by the spontaneous grafting of methoxy groups (144).…”
Section: Silicon In Non-aqueous Electrolytesmentioning
confidence: 98%